Positive psychology : advances in understanding adult motivation - Sinnott, Jan D. (Springer New York, 2013)
The study of Positive Psychology brings a much needed fresh emphasis to the study of the cognition, personality traits, and contexts of behavior that are associated with optimal development during the life course.  The field highlights the ways in which growth, hope, and resilience aid a person and motivate him or her in dealing with the inevitable challenges of life. Positive Psychology: Advances in Understanding Adult Motivation examines the traits and contexts of behavior that are associated with optimal development and resilience over the life course. The volume investigates individual psychological development through the stages of emerging adulthood, full adulthood, middle age, and old age.  It explores which personality traits and which aspects of the environment help a person to flourish, thrive, and grow. Moreover, the volume describes the development of resilience as well as other characteristics that will assist individuals in overcoming challenges throughout adult development. Accordingly, the chapters in this book each speak to one of the major portions of adult life that can be addressed in new ways by means of the relatively new discipline of Positive Psychology. The case studies are drawn from the entire field of Positive Psychology, from acceptance to teaching Positive Psychology, divided into four organizational and theoretical subsections about research and scholarship related to the creation or existence of:                 -positive subjective experiences;                 -positive personality traits;                 -positive environments; and                 -learning to thrive during adulthood.   This book will serve as an indispensable reference for both academics and practitioners who are using a positive psychology approach in their daily practice.